First order phase transition at the irreversibility line of Bi2Sr2CaCu2O8+δ - Pastoriza, H.; Goffman, M. F.; Arribére, A.; de la Cruz, F. (American Physical Society, 1994)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina